2005
DOI: 10.1021/ac053456d
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Enhanced Raman Spectroscopy

Abstract: mekal theoretically predicted inelastic light scattering in 1923 (1). Raman and Krishnan first experimentally observed the phenomenon and reported in their 1928 Nature paper that the inelastic scattering effect was characterized by "its feebleness in comparison with the ordinary scattering" (2). This "feeble" phenomenon is now known as Raman scattering. The change in wavelength that is observed when a photon undergoes Raman scattering is attributed to the excitation (or relaxation) of vibrational modes of a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
873
0
9

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,077 publications
(899 citation statements)
references
References 123 publications
17
873
0
9
Order By: Relevance
“…The inherent nanofibrous porosity also controls molecular diffusion which is critical in micro-spot sized optical spectroscopy techniques. 20,21 In this study, we have demonstrated controllable surface roughness and porosity which was directly related to SERS activity of BPA and DCFNa. These findings impact the SERS sensor pad development towards chemical and bio-molecular sensing applications.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…The inherent nanofibrous porosity also controls molecular diffusion which is critical in micro-spot sized optical spectroscopy techniques. 20,21 In this study, we have demonstrated controllable surface roughness and porosity which was directly related to SERS activity of BPA and DCFNa. These findings impact the SERS sensor pad development towards chemical and bio-molecular sensing applications.…”
mentioning
confidence: 70%
“…Since strong BPA adsorption is expected, fluorescence is attributed to a reduction in nanoparticle size. 21 As opposed to BPA, DCFNa was detected better under dry residue conditions given its high solubility under aqueous conditions. DCFNa structure can have two nonsymmetrical isomers with 58 irreducible vibration modes.…”
mentioning
confidence: 92%
“…Interested readers are directed to ref. 50 and 51 for more information about this technique. The sensitivity of LSPR to changes in dielectric environment and aggregation has also been harnessed to fabricate colorimetric sensors.…”
Section: Biomedical Applications Of Gold Nanostructuresmentioning
confidence: 99%
“…Nanometallic objects are able to trap incident radiation, focusing it into very small volumes. Gold nanoparticles have been used to concentrate electromagnetic fields to increase Raman scattering in a molecular identification technique known as surface-enhanced Raman spectroscopy (SERS) [8]. Nanoparticles may be used to control membrane processes via thermoplasmonics [9,10].…”
Section: Introductionmentioning
confidence: 99%